Visual and hearing impairments are associated with cognitive decline in older people. (25th April 2018) - Maharani, Asri; Dawes, Piers; Nazroo, James; Tampubolon, Gindo; Pendleton, Neil; ,
Abstract: Introduction: highly prevalagent hearing and vision sensory impairments among older people may contribute to the risk of cognitive decline and pathological impairments including dementia. This study aims to determine whether single and dual sensory impairment (hearing and/or vision) are independently associated with cognitive decline among older adults and to describe cognitive trajectories according to their impairment pattern. Material and methods: we used data from totals of 13, 123, 11, 417 and 21, 265 respondents aged 50+ at baseline from the Health and Retirement Study (HRS), the English Longitudinal Study of Ageing (ELSA) and the Survey of Health, Ageing and Retirement in Europe (SHARE), respectively. We performed growth curve analysis to identify cognitive trajectories, and a joint model was used to deal with attrition problems in longitudinal ageing surveys. Results: respondents with a single sensory impairment had lower episodic memory score than those without sensory impairment in HRS ( β = −0.15, P < 0.001), ELSA ( β = −0.14, P < 0.001) and SHARE ( β = −0.26, P < 0.001). The analysis further shows that older adults with dual sensory impairment in HRS ( β = −0.25, P < 0.001), ELSA ( β = −0.35, P < 0.001) and SHARE ( β = −0.68, P < 0.001) remembered fewer words compared with those with no sensory impairment. The stronger associations between sensory impairment and lower episodic memory levels were found in the joint model which accounted for attrition. Conclusions: hearing and/or vision impairments are a marker for the risk of cognitive decline that could inform preventative interventions to maximise cognitive health and longevity. Further studies are needed to investigate how sensory markers could inform strategies to improve cognitive ageing.